2016
DOI: 10.5406/amerjpsyc.129.3.0259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collective Transitions on the Organization and Contents of Autobiographical Memory: A Transition Theory Perspective

Abstract: In this article, we first outline a minimalist approach to the organization of autobiographical memory called transition theory. This theory assumes that the content and organization of autobiographical memory mirror the structure of experience and reflect the operation of basic memory processes. Thus, this approach rests on an analysis of the environment that emphasizes repetition, co-occurrence, change, and distinctiveness. We then report a study that tested a set of predictions derived from transition theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 92 publications
7
61
0
Order By: Relevance
“…There are, however, inevitable discontinuities in lives. Some scholars (Bohn & Habermas, 2015; Brown, 2016; Brown & Lee, 2010; Brown, Schweickart, & Svob, 2016; Enz & Talarico, 2015; Pillemer, 2009; Shi, 2017; Uzer & Brown, 2015) have drawn a distinction between turning points in lives, which are changes in life direction, such as St. Augustine’s conversion at Ostia (Saint Augustine of Hippo, 1997, pp. IX, x, 23–25), and transitions, which are external changes in daily circumstances, such as Primo Levi’s transport to Auschwitz in 1944 ( Levi, 1948/2015).…”
Section: The Benefits Of Modularized Livesmentioning
confidence: 99%
“…There are, however, inevitable discontinuities in lives. Some scholars (Bohn & Habermas, 2015; Brown, 2016; Brown & Lee, 2010; Brown, Schweickart, & Svob, 2016; Enz & Talarico, 2015; Pillemer, 2009; Shi, 2017; Uzer & Brown, 2015) have drawn a distinction between turning points in lives, which are changes in life direction, such as St. Augustine’s conversion at Ostia (Saint Augustine of Hippo, 1997, pp. IX, x, 23–25), and transitions, which are external changes in daily circumstances, such as Primo Levi’s transport to Auschwitz in 1944 ( Levi, 1948/2015).…”
Section: The Benefits Of Modularized Livesmentioning
confidence: 99%
“…When references to a specific public event or historical period are common in a population, H-DAPs have been formed and the LiH effect is evident (Brown, 2016). Studies found a LiH effect for wars (Bohn & Habermas, 2016;Brown et al, 2012Brown et al, , 2009Brown, Schweickart, & Svob, 2016;Brown & Lee, 2010;Zebian & Brown, 2014), the Cultural Revolution in China (Gu, Tse, & Brown, 2017), and the Izmit earthquake in Turkey (Brown et al, 2009). Moreover, these studies showed that the LiH effect was graded; i.e., it was more pronounced in populations whose everyday lives had been more affected than in less affected populations.…”
Section: The Living-in-history Effectmentioning
confidence: 99%
“…8 There are, however, inevitable discontinuities in lives. Some scholars (Bohn and Habermas, 2015;Brown, 2016;Brown and Lee, 2010;Brown et al, 2016;Enz and Talarico, 2015;Shi, 2017;Pillemer, 2009;Uzer and Brown, 2015) have drawn a distinction between turning points in lives, which are changes in life direction, such as St. Augustine's conversion at Ostia (Saint Augustine of Hippo, 1997, IX,…”
Section: Features Strands Sharementioning
confidence: 99%